The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 15th Annual International Conference on Mobile Computing and Networking 2009
DOI: 10.1145/1614320.1614352
|View full text |Cite
|
Sign up to set email alerts
|

A fundamental scalability criterion for data aggregation in VANETs

Abstract: The distribution of dynamic information from many sources to many destinations is a key challenge for VANET applications such as cooperative traffic information management or decentralized parking guidance systems. In order for these systems to remain scalable it has been proposed to aggregate the information within the network as it travels from the sources to the destinations. However, so far it has remained unclear by what amount the aggregation scheme needs to reduce the original data in order to be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…The main challenge for all of these beacon systems is their sensitivity to environmental conditions like vehicle density and network load. Besides, the scalability criterion must be investigated in order to make the system viable in real scenarios [11].…”
Section: Related Workmentioning
confidence: 99%
“…The main challenge for all of these beacon systems is their sensitivity to environmental conditions like vehicle density and network load. Besides, the scalability criterion must be investigated in order to make the system viable in real scenarios [11].…”
Section: Related Workmentioning
confidence: 99%
“…It has been shown that this type of aggregation schemes have scalability issues [20]. Moreover, the road segment-based group members have a common view of their environment which is achieved either by a multi-round scheme or by quantization.…”
Section: B Fuzzy Logic In Data Aggregationmentioning
confidence: 99%
“…This parameter is named as maximum photographic distance, denoted as mpd. How to regulate the orientation of camera for capturing image and how to deal with the image processing are beyond the scope of this paper, related works can be found in [19][20][21].…”
Section: Problem Statementmentioning
confidence: 99%